تطوراللغة العربية من العرب إلی شبه القارة (الهند وباکستان): The development of the Arabic language from the Arabs to the sub-continent (India and Pakistan) - Muhammad Abdul Rehman; Dr. Hafiz Faiz Rasool; Abbas Ali Raza (Al Manhal Research Journal, 2023)
God chose the Arab nation to convey the call of Islam to all nations, and their leadership chose the Arab prophet and our Messenger Muhammad (peace be upon him), so the Arabs carried this message with merit and fulfilled the trust with sincerity and sincerity in intention and action, and offered martyrs for it and endured trouble and hardship for it, and led liberation armies, to liberate man from worshiping idols to worshiping the one religion, and so that this light reaches everywhere, and they left the clan and the homelands for it and settled in distant lands to spread the principles of Islam pleasing to God and His Messenger. Islam entered the countries of India since the first issuance of the Islamic call during the era of the Commander of the Faithful, Umar ibn al-Khattab, may God be pleased with him, and the conquests expanded during the Umayyad era under the leadership of (Muhammad ibn al-Qasim al-Thaqafi). From the Nitrian monsters, then it was followed by migration after the Safavid attack on Iraq, and India was overwhelmed by the waves of Arab-Islamic immigration, and it was receiving these generous delegations with a wide-open heart, honoring their support and improving their benefit, and competing in the largest number of scholars, gentlemen, supervision, and people of virtue and righteousness who seek refuge in it and considers their presence a pride that is not above it. Among them emerged the scholars, writers, poets, and virtuous men who devoted themselves to seeking knowledge, teaching it, and spreading the principles of Islam. Thanks to their blessed efforts, the Islamic call and the Arabic language, the language of the Great Qur’an, flourished in a way that was not known in any other Islamic country during those centuries that witnessed a general decline in science, thought, and writing in the Arab world, which was intensified by the Tartar campaign that destroyed the Arab-Islamic civilization in Baghdad in its golden age.